ANALISIS PERBANDINGAN PENDAPATAN USAHATANI KARET POLA EKS UPP TCSDP DAN POLA SWADAYA DI DESA KOTO DAMAI KECAMATAN KAMPAR KIRI TENGAH KABUPATEN KAMPAR - Tika Yuliyanti; Yusmini Yusmini; Susy Edwina (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
The purpose of this study was to analyze and compare the net income between rubber farmers Ex UPP TCSDP pattern and Swadaya pattern in the Koto Damai Village Kampar KiriTengah District Kampar Regency . The analysis is the analysis of net income and the t test . The method used is survey by census sampling technique as much as 20 farmers Pattern Governmental and simple random sampling technique as much as 20 farmers Ex UPP TCSDP.Analysis results showed an average net income of farmers rubber Ex UPP TCSDP Pattern is 33 % larger than the SwadayaPattern . T test is greater than t table at the level of 95 %, which means there is a real difference in net income between rubber farmers Ex UPP TCSDP Pattern and Swadaya Pattern, income disparity is due to the difference in the amount of rubber production and the use of production factors between the second pattern rubber farming. Keywords: Comparison, Income, Ex UPP TCSDP Pattern, Swadaya Pattern